“Alanina aminotransferasa, proteínas y electrolitos en juveniles de tilapia roja (Oreochromis mossambicus x oreochromis niloticus) alimentados con Quitosano en dieta.” - Zambrano Sánchez, Jonathan Emilio (2020)
The main objective of this research was the evaluation of the effect of chitosan in a pelleted diet where the metabolic response of electrolytes, alanine aminotransferase and proteins in juvenile red tilapia (Oreochromis mossambicus x Oreochromis niloticus) was examined. For which, 6 treatments with three repetitions were handled in a DCA. Each of these treatments was distributed from an experimental diet with different inclusion of chitosan at (0, 1, 2, 3, 4 and 5%). Where it was established that the highest electrolyte metabolic response occurred in treatments T3 and T5 with inclusion of 3% and 5% chitosan for calcium, while in potassium it was demonstrated in treatments T3 and T4 with inclusion of 3% and 4% chitosan . There was no statistical difference in the alanine aminotransferase enzyme, however the highest value was presented in T0 and T3 (0% and 3% chitosan in the diet). In proteins, there was a significant difference in total proteins, even so, finding a greater elevation in T3 and T2 (3% and 2% of chitosan in the diet) in albumin and for globulin there was a higher concentration in T0 and T1 (0% and 1% chitosan in the diet) where it is concluded that according to the statistical analysis, a significant difference was found for total proteins, globulin albumins, finding a greater elevation for proteins in T3 and T2, as well as for albumin in terms of globulins higher concentration in T2 and T3; Alanine aminotransferase showed significant differences for the treatments, higher values were found in T2 and T5 where almost no difference was obtained and that the content of electrolytes in potassium, calcium showed significant differences, higher values were found in T3 and T4 for calcium , as well as potassium for tilapia fingerlings. I conclude that feeding chitosan under diets shows us that there are significant differences in total proteins; alanine aminotransferase and electrolytes. Key words: albumin, pelleted feed, biostimulant, blood plasma, metabolic response.